Impact of Ascites in Pulmonary Function of Patients with Portal Hypertension (Medical Forum Monthly, 2020)
Objective: To evaluate the pulmonary function of patients having portal hypertension with altered volume of ascites.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Pulmonology, Faisalabad Medical University, Faisalabad and Abwa Hospital / Research centre Faisalabad from July, 2019 to December, 2019.Materials and Methods: Fifteen patients with portal hypertension and ascites underwent pulmonary function tests, consisting of spirometry and arterial blood gases, before and after reducing the volume of ascites. The parameters analyzed were: forced vital capacity (FVC); expiratory reserve in the first second (FEV 1); expiratory flow between 25 and 75% of FVC (FEF25-75%); Force expiratory volume 6(FEV6); FEV1 ratio/ FVC; PEF, arterial oxygen pressure (PaO2), carbon dioxide arterial pressure (PaCO2) and oxygen saturation (SaO2).Results: There was a significant improvement in the lung volumes analyzed after decreasing ascites with diuretic treatment associated or not with paracentesis.Conclusion: We conclude that in patients with portal hypertension and ascites, there is a decrease in lung volumes in relation to the predicted values, with significant improvement after a decrease in ascites. Likewise, we observed an increase in PaO2 and SaO2.